VERONICA'S MOTIVATION TO SAVE THE NATION REFLECTED IN JOEL SCHUMACHER'S VERONICA GUERIN (2003): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PUTRO , PRASETYO LUKMONO (2010)
The major problem of this study is how the motivation from Veronica Guerin is reflected in Veronica Guerin. The objective of this study is to analyze the movie based on its structural elements, and based on individual psychological approach. The benefits of the study are to give the application of individual Psychological approach in literary study. This study belongs to the qualitative study. The object of the study is Joel Schumacher's Veronica Guerin movie published in 2003 by Touchstone pictures and movie script. The primary data source is the main data obtained from all the images which form such as the scene of the movie itself and the texts which form such as words, phrases, and sentences in dialogues or monologues occurring in the movie related to the topic. And the secondary data sources are the others data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by note-taking for the texts and image-capturing for the images. The technique of data analysis used in this study is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, it is apparent that in this movie Joel Schumacher conveys a moral message that having motivation is one of the positive ways to change life. Second, based on the psychological analysis, it is evident that in this movie, Joel Schumacher wants to give the real phenomenon of psychology that physical defect on Veronica Guerin as a journalist shall not be a problem in revealing the truth.